PSYCHOLOGICAL MECHANISMS OF STUDENTS’ SELF-IMPROVEMENT IN THE ACTIVITIES OF MILITARY ACADEMIC LYCEUMS - Ergashev Doniyor (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This article comprehensively analyzes the psychological mechanisms of students’ self-improvement within the environment of Temurbek Military Academic Lyceums. The relevance of the study arises from the necessity to provide a psychological foundation for the personal development of cadets in the modern military education system. The research examines the interrelationship between emotional regulation mechanisms, cognitive processes, and metacognitive processes. The findings demonstrate that in the environment of military-oriented academic lyceums, self-development is effectively achieved through reflexivity, metacognitive control, and emotional reappraisal.